PSV-B-17 Additional dietary choline increases serum metabolites as determined by direct infusion mass spectrometry in post-gonadectomy kittens. (8th October 2021) - Godfrey, Hannah; Rankovic, Alexandra; Grant, Caitlin E; Shoveller, Anna-Kate; Abood, Sarah; Bakovic, Marica; Verbrugghe, Adronie
Abstract: This study aimed to investigate changes in serum metabolites using direct infusion mass spectrometry (Di-MS) after 12 weeks with or without additional choline in growing, post-gonadectomy kittens. The present study was approved by the University of Guelph Animal Care Committee (AUP#4118). Intact, male kittens (3-months old; n = 15) were fed a base-diet to growth requirements (3310mg choline/kg DM) over an 11-week acclimation. Kittens were gonadectomized (week 1) and assigned to base-diet (n = 7) or base-diet with 300mg/kgBW 0.75 additional choline (n = 8) and fed to mimic ad libitum food intake (3 meals totaling thrice daily requirements) for 12-weeks. Fasted serum samples were obtained and analyzed for 130 metabolites via Di-MS (week 0 and 12). The proc GLIMMIX procedure (SAS) was used to analyze differences between groups as a repeated measure. Additional choline resulted in higher serum concentrations of one-carbon metabolites such as methionine, serine, betaine, and sarcosine (P < 0.05). As expected, serum concentrations of phosphatidylcholines increased with additional choline, as did serum concentrations of lysophosphatidylcholines and sphingomyelins, compared to no additional choline (P < 0.05). There was minimal impact on acyl carnitines with a decrease in medium length acyl carnitines (P < 0.05). Additionally, there was an increase in serum concentrations of spermine, trans hydroxyproline, methionine sulfoxide, proline, and indole acetic acid, and a decrease in serum trimethylamine N-Oxide compared to control (P < 0.05). Effects of growth stage or gonadectomy may have resulted in increased serum amino acid concentrations such as asparagine, glutamine, glutamic acid, histidine, lysine, methionine, threonine, and tyrosine in both groups (P < 0.05). These results may indicate benefits for providing additional choline to post-gonadectomy kittens on one-carbon metabolism and fatty acid oxidation which could promote healthy weight and body condition. However, more research is warranted to further understand choline's role in energy balance and its potential in prevention and treatment of feline obesity.